2019
DOI: 10.1002/lary.28069
|View full text |Cite
|
Sign up to set email alerts
|

Integrative resident education curriculum to adapt to the modern otolaryngology trainee

Abstract: Objectives/Hypothesis To examine the perspectives of current otolaryngology–head and neck surgery residents and faculty members on educational formats and approaches. To assess the effects of a novel integrative educational curriculum for residents by examining results from the otolaryngology training examination (OTE). We hypothesized that altering the current curriculum to accentuate resident participation would result in improved performance on the OTE. Study Design Prospective cohort study. Methods We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[18] Howard S Moskowitz et al suggested this type of curriculum, which combined a variety of approaches including a flipped classroom model with active participation and integrates app technology, could improve otolaryngology-head and neck surgery residents performance on educational assessments. [19] Eunicia Tan et al suggested that flipped classroom showed promise as an acceptable approach to in-house emergency medicine teaching. [20] All the above represented flipped teaching had achieved good feedback and application effect for residents training in the field of different clinical specialties.…”
Section: Interpretation Of Relevant Data In the Studymentioning
confidence: 99%
“…[18] Howard S Moskowitz et al suggested this type of curriculum, which combined a variety of approaches including a flipped classroom model with active participation and integrates app technology, could improve otolaryngology-head and neck surgery residents performance on educational assessments. [19] Eunicia Tan et al suggested that flipped classroom showed promise as an acceptable approach to in-house emergency medicine teaching. [20] All the above represented flipped teaching had achieved good feedback and application effect for residents training in the field of different clinical specialties.…”
Section: Interpretation Of Relevant Data In the Studymentioning
confidence: 99%
“…The majority of current surgical trainees have been exposed to virtual learning environments from an early age, are quick to adapt to these formats (Larvin, 2009) (Martinelli et al, 2019), and frequently incorporate online media in preparation for credentialing exams and clinical practice (Shabli et al, 2019). Flipped classroom models have been demonstrated to improve performance (Moskowitz & Hsueh, 2020). Current AHNS e-resources include standardized goals and objectives and recommended syllabus (Service, 2018), as well as online journal clubs and surgical videos for regional and free flap harvests.…”
Section: Online Resourcesmentioning
confidence: 99%
“…[18][19][20] Studies investigating the efficacy of in-lecture question bank utilization in surgical resident education do not currently exist; while similar approaches within flipped classroom literature do exist, no current studies use a cohort comprised of only general surgery residents. 14,21,22 Surgical residents within these studies were found to have higher lecture engagement, increased participation, and superior performance on educational assessments. Furthermore, when utilized outside the classroom, commercial question banks improve resident knowledge of basic science, as well as performance on formal assessments.…”
Section: Discussionmentioning
confidence: 76%